Peningkatan Kreativitas Peserta Didik pada Materi Statistika Melalui Model Pembelajaran PjBL-STEM Kelas XII MIPA 6 SMA Negeri 7 Yogyakarta - Ida Lydiati (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
This study aims to find out how to improve students' creativities in statistics through the PjBL-STEM class XII MIPA 6 SMA Negeri 7 Yogyakarta. This research is a classroom action research conducted during two cycles, where each cycle consists of planning, action, observation, and reflection. The results showed that to increase the creativity of students in statistics through the PjBL-STEM learning model can be done by: (a) reflection, namely students learn statistics as part of mathematics about the the measures of central tendency and measures of variability using technology such as calculator or computer to process the measures of central tendency and measures of variability of data about height and weight; (b) research, namely students conducting research searching for information from various relevant sources in developing understanding that is relevant to the project being carried out related to science about BMI (Body Mass Index); (c) discovery, namely students use information obtained when conducting research to develop projects. Students are trained to build cooperation in groups and collaborate to present alternative problem solutions that make it easy for them to process data using technology in BMI calculator designs and posters; (d) application, namely students learn to connect various discipline in STEM, test products or solutions that have been previously determined, and then make improvements to the BMI calculator and poster; (e) presentation, namely students communicate products or solutions between students in classroom or the wider community using technology in poster that equipped with QR-Code.